A Comparative Study on the Quality of Available Brand and Non Brand Fluid Milk Consumed by the People of Chittagong City of Bangladesh - Debnath, GK; Kober, AKMH; Chanda, T; Chanda, GC; Bari, MS (International Journal of Natural Sciences, 2016)
The study was undertaken to have a comparative investigation on the quality of available brand and non-brand fluid milk consumed by the inhabitants of Chittagong City (CC). Milk samples were collected from the city vendors, departmental stores, households and dairy farms. A total of 100 samples were analyzed for nutritional (percentage of butter fat, solids-not-fat and protein), chemical (pasteurization test, added preservatives and adulteration status) and microbial (standard plate count and coliform count) parameters to evaluate the quality of the collected milk samples. The study reveals that the collected milk samples show significant (P?0.01) variation in nutritional, chemical and microbiological parameters among the sources. All brands milk samples were properly pasteurized. The quality of milk samples from local farms was good except coliform counts. All the samples possessed high coliform counts. The quality of farm produced milk and rural milk were deteriorated by middlemen due to adulteration with water. Water adulteration was detected in 68% and 54% of the milk samples in case of vendor supplied rural and vendor supplied farm milk respectively. Most alarming fact is more than 10% milk samples contained formalin in case of vendor supplied rural milk. It may be concluded that both the vendor supplied rural milk and vendor supplied farm milk were low quality due to water adulteration and added formalin preservatives respectively. International Journal of Natural Sciences (2014), 4(1) 16-20